2018
DOI: 10.3857/roj.2018.00164
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of proton therapy for patients with chordomas

Abstract: PurposeTo investigate the clinical outcome of proton therapy (PT) in patients with chordoma.Materials and MethodsFifty-eight patients with chordoma treated with PT between June 2007 and December 2015 at the National Cancer Center, Korea, were retrospectively analyzed. The median total dose was 69.6 cobalt gray equivalent (CGE; range, 64.8 to 79.2 CGE). Local progression-free survival (LPFS), distant metastasis-free survival (DMFS), overall survival (OS), and diseasespecific survival (DSS) rates were calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Therefore, particle therapy is preferred over conventional radiotherapy therapy to deliver a sufficient dose to the designated site. The LC rate has been reported to be 69.7%–87.9% [ 31 34 ] with an OS rate range of 80%–88.3% at 5 years [ 31 33 ]. For sacral chordoma, a similar outcome has been reported for PBT [ 34 36 ].…”
Section: Clinical Applications Of Cptmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, particle therapy is preferred over conventional radiotherapy therapy to deliver a sufficient dose to the designated site. The LC rate has been reported to be 69.7%–87.9% [ 31 34 ] with an OS rate range of 80%–88.3% at 5 years [ 31 33 ]. For sacral chordoma, a similar outcome has been reported for PBT [ 34 36 ].…”
Section: Clinical Applications Of Cptmentioning
confidence: 99%
“…The LC rate has been reported to be 69.7%–87.9% [ 31 34 ] with an OS rate range of 80%–88.3% at 5 years [ 31 33 ]. For sacral chordoma, a similar outcome has been reported for PBT [ 34 36 ]. Although direct comparison of photon and particle therapy has not been reported, a recent analysis of 863 patients with chordoma and chondrosarcoma from the National Cancer Center Database showed that PBT was associated with an improved OS compared to photon radiotherapy [ 37 ].…”
Section: Clinical Applications Of Cptmentioning
confidence: 99%
“…The observed 5 year local tumour control was 92.8 and 63.0% for patients treated with ≥69.6 and<69.6 Gy, respectively. 61 Likewise, an analysis of 863 chordoma patients captured in the National Cancer Data base has shown undisputedly that dose for chordoma was associated with a significant increase in OS on univariate analysis. 1 Other proton series have shown such a dose-response with sbC.…”
Section: Skull-base Tumoursmentioning
confidence: 99%
“…Chordoma is a rare primary bone tumor, which develops from intraosseous notochordal remnants along the neuroaxis [ 1 ]. Therefore, it commonly occurs at the sacrococcygeal region (50%) or base of the skull (35%) and rarely occurs at the mobile spine (15%) or the lumbar spine (6%) [ 2 3 ].…”
Section: Introductionmentioning
confidence: 99%